In planta ANALYSIS OF SALICYLIC ACID MEDIATED MANAGEMENT OF - Fahima Firdouse .M; Sudha .A; Johnson .I; Anandham .R; Saranya .N; Selva amala .A; Arunparakash .S (Journal of Animal and Plant Sciences, 2024)
Bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae (Xoo) is a catastrophic bacterial disease of rice, and researchers are facing difficulties in developing the management practices, whereas the continued use of bactericides viz, streptomycin, copper oxychloride leads to the development of resistant Xoo strains. As a consequence, the development of an environmentally safe bactericide for the management of this devastating disease is needed. The present study focused on identification of effective synthetic activators against bacterial leaf blight in rice during their interaction. Survey was conducted to collect different isolates of Xoo and their morphological characters and biochemical properties were determined. All the 10 isolates exhibited circular to flattened slimy yellow colour colonies of the pathogen and showed positive reaction for citrate utilization, lysine utilization and ornithine utilization test. All the ten isolates showed negative reaction for sorbitol utilization. The collected isolates were subjected to PCR for the amplification of 16S-23S intergenic regionwith the species specific primer and obtained amplicon at ⁓470 bp for the confirmation at molecular level. The virulentisolate wasidentified by measuring biofilm formation and xanthomonadin pigment which revealed that the isolate ADT 53 strain T3 with the accession number OR121377 recorded maximumOD value of 0.356 for biofilm formation at 570 nm and 0.686 for xanthomonadin pigment at 445 nm. In planta studies revealed that salicylic acid at 100 ppm has the maximum inhibitory effect against bacterial leaf blight disease with the minimal lesion size of 0.7 cmcompared to negative control (water).
Keywords: Keywords : Activators; BLB; Biofilm; Characterization; In planta; Xanthomonadin